A facile synthesis of Pt@Ir zigzag bimetallic nanocomplexes for hydrogenation reactions1. Issue 44 (4th June 2015) - Wang, Jiaqing; Ge, Danhua; Cao, Xueqin; Tang, Minghua; Pan, Yue; Gu, Hongwei
<x xml:space="preserve">Abstract</x> A facile approach for the synthesis of Pt@Ir zigzag bimetallic nanocomplexes with high catalytic activity.